THE EFFECT OF THE NUMBERED HEADS TOGETHER COOPERATIVE LEARNING MODEL ON STUDENTS' LEARNING VALUES IN THE ECONOMICS SUBJECT IN CLASS XI PRIVATE SENIOR HIGH SCHOOL TAMAN SISWA PEMATANGSIANTAR ACADEMIC YEAR 2025/2026 - Yesica Destri Turnip; Tumpal Manahara Siahaan; Injen Pardamean Butarbutar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to determine the Effect of the Numbered Heads Together Cooperative Learning Model on Student Learning Scores in the Economics Subject of Class XI of Tamansiswa Private High School Pematangsiantar in the 2025/2026 Academic Year. The type of research used in this study is quantitative with a quasi-experimental design through a Nonequivalent Control Group Design. The study population consisted of all students of class XI Merdeka of Tamansiswa Private High School Pematangsiantar with a total of 102 students. The sample used in this study consisted of 2 classes, namely class XI Merdeka 7 as the control class and class XI Merdeka 8 as the experimental class with a total of 69 students. Based on the results of the study, it shows that the learning scores of students who do not use conventional methods obtain an average score of 79.892. While the learning scores of students who use the Numbered Heads Together cooperative model obtain an average score of 93.125. The t-test results also support this research, where the t-count value is 6.682 and the t-table value is 1.996, where the t-count > t-table with a significance level of 0.05. Thus, Ho is rejected and Ha is accepted. This proves that there is a significant influence of the Numbered Heads Together cooperative learning model on student learning scores in the Economics subject of class XI at Tamansiswa Private High School, Pematangsiantar.